2010
DOI: 10.1055/s-0030-1261963
|View full text |Cite
|
Sign up to set email alerts
|

The CB-1 Receptor Antagonist Rimonabant Modulates the Interaction Between Adipocytes and Pancreatic Beta-Cells in Vitro

Abstract: Our data show that rimonabant modulates the adipocyte - beta-cell interaction with respect to beta-cell proliferation and indicate that signalling molecules other than adiponectin and components of the Wnt pathway mediate this cross-talk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The effects of SR141716A on insulin secretion in vitro and in vivo in rodents have been a point of controversy in the literature. Thus, it is reported to decrease insulin hypersecretion in islets isolated from diabetic rats [36] and glucose-induced insulin secretion from mouse islets [37], but another study showed that SR141716A did not significantly affect insulin secretion from mouse islets [38]. Conversely, SR141716A was found to reversibly stimulate insulin secretion from human islets [39], and its chronic administration improved islet function and morphology in diabetic rats [40].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of SR141716A on insulin secretion in vitro and in vivo in rodents have been a point of controversy in the literature. Thus, it is reported to decrease insulin hypersecretion in islets isolated from diabetic rats [36] and glucose-induced insulin secretion from mouse islets [37], but another study showed that SR141716A did not significantly affect insulin secretion from mouse islets [38]. Conversely, SR141716A was found to reversibly stimulate insulin secretion from human islets [39], and its chronic administration improved islet function and morphology in diabetic rats [40].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, leptin-and rimonabantcaused inhibition of AMPK may result in the observed synergistic effects on food intake (Boustany-Kari et al 2011). In addition, rimonabant increases the expression of adiponectin by adipocytes (Bensaid et al 2003;Despres et al 2005), and this is supposed to be one reason for the improved insulin sensitivity with rimonabant observed in vivo ( € Ulgen et al 2011). Inhibition of peripheral CB1 receptors in adipocytes directly promotes transdifferentiation of white adipocytes into a mitochondria-rich, thermogenic brown fat phenotype, resulting in enhanced thermogenesis and insulin sensitivity (Perwitz et al 2010).…”
Section: Rimonabantmentioning
confidence: 99%